Assessment of Tourism Development in Belarus: A Comprehensive Analysis of Infrastructure, Cultural Heritage and Natural Resources - Kauchun, Viktoryia; Michalska, Anna; Zukow, Walery (Journal of Education, Health and Sport, 2024)
Background: Tourism development is a significant factor in socio-economic growth, particularly in countries undergoing transition. Belarus, with its rich cultural heritage and natural resources, presents an interesting case study for analyzing tourism development patterns and challenges. Purpose: This study aims to evaluate tourism development in Belarus during 2010-2023, focusing on infrastructure quality, cultural heritage utilization, and natural resource management. The research examines key factors influencing tourism development and assesses their relative impact on the sector's growth. Materials and methods: The study employed a mixed-methods approach, utilizing a quantitative survey (n=100) of local stakeholders across six regions of Belarus. The research instrument included 17 structured questions measuring perceptions of tourism development across multiple dimensions. Data analysis was conducted using chi-square tests and Cramér's V coefficient to determine statistical significance and relationship strength. Results: The findings indicate moderate tourism development in Belarus (39% rated it as average, 42% as high). Infrastructure quality shows significant regional variation (χ2(4)=31.50, p<0.001, V=0.56). Cultural heritage emerged as a primary attraction (72% agreement), while natural resources received varied evaluations (57% highlighting landscape value). Key development barriers identified include visa restrictions (74% of respondents), insufficient marketing (62%), and underdeveloped transport infrastructure (51%). Conclusions: The study reveals that Belarus's tourism development exhibits a complex pattern of strengths and challenges. While the country possesses significant potential through its cultural heritage and natural resources, its tourism development is constrained by structural barriers. The findings suggest that future tourism growth requires systematic infrastructure modernization, reform of visa policies, and development of comprehensive marketing strategies.